Flood-Resilient Mass Transit Planning in Ouagadougou - World Bank (World Bank, Washington, DC, 2021)
Ouagadougou, the largest city in Burkina Faso, is growing rapidly, with the annual rate reaching 9 percent by some estimates, and with commensurate challenges for ensuring efficient mobility for its residents. Like many urban areas in Sahelian West Africa, Ouagadougou is also highly vulnerable to extreme hydro-meteorological events. In the context of the plans to develop an efficient, bus-based mass transit system in Ouagadougou in the medium term, the study aimed to characterize the spatial distribution and severity of flood risk affecting the planned system; and to identify, evaluate, and prioritize interventions that will increase its resilience. The study focuses on a pilot sector of 67 km, covering a large part of central Ouagadougou and its strategic infrastructures, at the intersection of the future planned mass transit system and the areas of the city a priori considered more flood prone (for example, near the major dams). By working with a local drone operator and an international flood modelling firm, the study constructed high spatial resolution digital elevation and digital terrain models for the area of interest (AOI), which served as inputs for developing a hydrological model. To further classify the road and future mass transit sections in order to prioritize interventions, the analysis applied the criteria of an area priority score and a flood criticality score, which together combine into an overall impact score. The importance of good planning and policy and regulatory actions vis-a-vis more structural engineering solutions is underlined by the fact that the top two measures singled out by the multicriteria analysis are so-called soft solutions - related to the maintenance and cleaning of the flood-related structures and the reinforcement of the waste collection system.